ANALISIS KOORDINASI ANTAR STAKEHOLDERS DALAM PROGRAM PENGEMBANGAN KOTA HIJAU DI KOTA BANDAR LAMPUNG - Dewie Brima Atika; Ratna Suminar (P3M STISIPOL Dharma Wacana Metro, 2018)
Coordination is an important role in an organization to achieve the desired goals. To achieve effective coordination, which includes communication, clear objectives, and the existence of good relationships. Therefore the Bandar Lampung city government should realize effective cooperation, in realizing good city development, namely the green city program. This paper aims to get an overview of coordination between agencies in implementing a green city development program in Bandar Lampung and also to identify factors that constrain coordination in green city development programs in Bandar Lampung This paper focuses on the coordination carried out between agencies in the green city development program carried out by related agencies such as Bappeda, the Sanitation and Parks Service, the City Planning Office, and BPPLH. In uncovering this problem, researchers used the theory of Nine conditions to achieve the coordination of Tripathi and Reddy, and several other supporting theories. This type of research is descriptive research with a qualitative approach. This research was conducted at the related agencies in Bandar Lampung City. The results and conclusions from this study are the ineffectiveness of the coordination of the Bandar Lampung city government in the green city development program. Of the nine conditions to achieve coordination only five conditions can work. Constraints faced include obstacles to ineffective communication between SKPD, lack of understanding of SKPD about programs and the validity period of green city programs.